Locked nucleic acid (LNA) enhances binding affinity of triazole-linked DNA towards RNA - Kumar, P; El-Sagheer, AH; Truong, L; Brown, T (Royal Society of Chemistry, 2017)
Oligonucleotides containing internal triazole-3'-LNA linkages bind to complementary RNA with similar affinity and specificity to unmodified oligonucleotides, and significantly better than oligonucleotides containing triazole alone. In contrast LNA on the 5'-side of the triazole does not stabilise duplexes. Triazole-LNA confers great resistance towards enzymatic degradation relative to LNA alone.